2015
DOI: 10.4238/2015.september.9.20
|View full text |Cite
|
Sign up to set email alerts
|

Sperm chromatin dispersion by formaldehyde in Wistar rats

Abstract: ABSTRACT. Formaldehyde (FA) is an environmental xenobiotic, which is genotoxic and carcinogenic to humans and animals; it induces DNA damage, mutations, and clastogenicity during critical cytogenetic events. FA-mediated oxidative stress is an important mechanism that has been associated with the induction of cytotoxic and genotoxic damage. Therefore, the objective of this study was to evaluate the dispersion of sperm chromatin and reproductive parameters induced by exposure to .0 ± 7.87, respectively; P = 0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
4
2
0
Order By: Relevance
“…The present findings, ie, long-term exposure to FA was associated with significant reductions in sperm motility, morphology, and DFI, were in agreement with animal studies . Significantly, nearly all the animal studies reported that FA exposure could decrease sperm number; however, similar declines were not observed in our study nor in the study by Wang et al The differences might result from different doses and time of exposure.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present findings, ie, long-term exposure to FA was associated with significant reductions in sperm motility, morphology, and DFI, were in agreement with animal studies . Significantly, nearly all the animal studies reported that FA exposure could decrease sperm number; however, similar declines were not observed in our study nor in the study by Wang et al The differences might result from different doses and time of exposure.…”
Section: Discussionsupporting
confidence: 91%
“…The present findings, ie, long-term exposure to FA was associated with significant reductions in sperm motility, morphology, and DFI, were in agreement with animal studies . Significantly, nearly all the animal studies reported that FA exposure could decrease sperm number; however, similar declines were not observed in our study nor in the study by Wang et al The differences might result from different doses and time of exposure. Animals were exposed to a relative high dose (10 mg/m 3 ) for a short period (<35 d), while humans were exposed to a relatively low dose (0.22-5.43 mg/m 3 ) for a longer period (>24 months).…”
Section: Discussionsupporting
confidence: 91%
“…The reduction of sperm quality in the present study indicates negative effects of oxidative stress induced by FA on male reproductive system. Several other studies have indicated the adverse effects of FA on sperm parameters (6,7,33,34) and our study is in line with them. FA has ability to cross the blood-testis barrier and induces oxidative stress by producing ROS which leads to degeneration of germ cells and disruption of spermatogenesis (6,33).…”
Section: Discussionsupporting
confidence: 92%
“…Henkel et al (36) demonstrated a direct correlation between sperm motility and decline in Leydig cells. A direct relationship between the FA exposure and dispersion of DNA chromatin of sperm was found by Betancourt-Martínez et al (34). In this research, Ginger extract improved sperm parameters when administrated simultaneously with FA.…”
Section: Discussionsupporting
confidence: 68%
“…RONS are produced in high quantities by endogenous metabolisms which are represented primarily by the activation of neutrophils, the products of cyclooxygenase (COX), lipoxygenase (LOX), and nitric oxide synthases (NOS) [ 1 3 ]. At the same time, RONS are also produced in the body through exogenous factors including formaldehyde (FA), particulate matter (PM), metals, and quinones [ 4 9 ].…”
Section: Introductionmentioning
confidence: 99%